Design, development and evaluation of an accelerometer array column for slope stability monitoring - Dumo, Rudolf
A device for monitoring underground deformations and movement was developed. The device is a segmented PVC pipe column that is inserted to a borehole through the suspected slope. Each segments' tilt with respect to the vertical is measured using dual axis MEMS accelerometers and relay the information to a master microcontroller, located at a device box at the surface, through CAN bus communications. The master microcontroller saves the tilt information to an on-site MMC card and further relay it to a remote database for storage via a WIFI link. A graphical use interface was also provided for processing data to a useful information to the end users.